Analisis Fiqh Muamalah Kontemporer Terhadap Mekanisme Qabdh dan Kepastian Hukum dalam Penerapan Smart Contract Pada Akad Murabahah Digital - Elma, Zainal Said (Program Studi Ekonomi Syariah IAIN Parepare, 2026)
This study aims to analyze the validity of the qabdh mechanism and legal certainty in the implementation of smart contracts within digital murabahah contracts from the perspective of contemporary Fiqh Muamalah. As the digitalization of Islamic finance continues to expand rapidly, critical challenges have emerged regarding the validity of contractual pillars due to the rigid and irreversible nature of blockchain-based automation. This normative legal research employs conceptual and statutory approaches. The findings indicate that the transformation of murabahah contracts into self-executing program code is Sharia-compliant, provided that the algorithm ensures a proper sequence of asset ownership (milkiyyah tammah) by the bank before its transfer to the customer, thereby preventing the defect of bai' al-ma'dum (the sale of a non-existent asset). Critically, the study finds that potential system errors or bugs within the program code may introduce elements of gharar (uncertainty). Therefore, ensuring legal certainty for all parties requires operational risk mitigation through digital escrow clauses integrated with positive law. In conclusion, the validity of smart contract-based murabahah depends on the synchronization between the accuracy of binary code execution and the transparency of Sharia principles.